Techno-economic assessment and environmental impacts of Mineral Carbonation of industrial wastes and other uses of carbon dioxide - Mehleri,ED; Bhave,A; Shah,N; Fennell,P; MacDowell,N (2015)
In this contribution, we present the results of an in-depth techno-economic analysis of some leading CO2 capture and utilisation (CCU) and conversion (CCC) options. Specifically, we consider CO2 conversion to methanol, formic acid and urea (CCC) in addition to mineral carbonation of industrial wastes (CCU). We compare the CCC and CCU options using a range of key performance indicators (KPIs), including 2nd law efficiency, CO2 avoided and tonneCo2/tonneproduct. The results indicate that CCU and CCC technologies are unlikely to provide a significant contribution to mitigating anthropogenic climate change. The primary bottleneck to industrial scale deployment of CCC technologies is likely to be the cost effective availability of low carbon-hydrogen in the case that the conversion option requires hydrogen. Further, we find that mineral carbonation may have niche applications in the context of industrial waste remediation but the large scale deployment of this technology as a substitute for the geological sequestration of CO2 is unlikely to be either cost effective or scalable. Moreover, although formic acid offers attractive economic profiles, we note that this process is at a lower TRL (TRL 4-5). Thus, we conclude that CCC and CCU technologies are only likely to be viable at scale in the event that substantial subsidies are available to offset the high costs associated with producing renewable hydrogen and the thermodynamic cost associated with processing such a stable molecule.